Awareness and utilization of pre-exposure prophylaxis and HIV prevention services among transgender and non-binary adolescent and young adults - Rodriguez, Arianna; Horvath, Keith J.; Dowshen, Nadia; Voss, Raina; Warus, Jonathan; Jacobs, Megan; Kidd, Kacie M.; Inwards-Breland, David J.; Blumenthal, Jill (Frontiers in Reproductive Health, 2024)
Transgender and gender non-binary (TGNB) individuals are disproportionally affected by HIV and face high rates of discrimination and stigmatization, resulting in limited access to HIV prevention services. Pre-exposure prophylaxis (PrEP) is highly efficacious for reducing the risk of HIV transmission. However, little research is available regarding PrEP awareness and utilization among TGNB adolescents and young adults (AYA). TGNB AYA ages 15-24 years old were recruited between December 2021 and November 2022 for participation in a one-time, anonymous online survey study to assess PrEP awareness and perceptions, as well as barriers to its use. Participants were recruited from seven academic centers offering gender-affirming care to TGNB AYA across the United States. Of the 156 TGNB AYA individuals who completed the survey, most (67%) were aware of PrEP; however, few (7%) had been prescribed PrEP. Many (60%) had not spoken to a medical provider and, even if the medication was free and obtained confidentially, most participants did not plan to take PrEP due to low perceived HIV risk, lack of PrEP knowledge, and concern about interactions between their hormone therapy and PrEP. These findings underscore the need for broad PrEP educational efforts for both TGNB AYA and their providers to improve knowledge, identify potential PrEP candidates among TGNB AYA and improve access by addressing identified barriers.